The influence of social trust, place attachment, and self-efficacy on farmers' commitment to agricultural land in Sukoharjo, Central Java, Indonesia - DHANU MUKTI WIBOWO; ERLIS SAPUTRA; SUDRAJAT SUDRAJAT (Smujo International, 2026)
Abstract. Wibowo DM, Saputra E, Sudrajat. 2026. The influence of social trust, place attachment, and self-efficacy on farmers' commitment to agricultural land in Sukoharjo, Central Java, Indonesia. Asian J Agric 10 (1): g100163. https://doi.org/10.13057/asianjagric/g100163. The sustainability of agricultural practices in Indonesia, as a developing country, is threatened by land conversion, with non-agricultural uses continuing to put pressure on agricultural land. This situation, which further weakens farmers' commitment to agricultural land and related activities, demands cooperative behavior from farmers and institutions, reflecting the presence of social trust. This study empirically examines how to verify the relationship between interpersonal and institutional trust and farmers' commitment to agricultural land use and ownership. It integrates place attachment and self-efficacy as mediators and examines the relationship between farmers' commitment to agricultural land use and their ownership of that land. Structural Equation Modeling (PLS-SEM) was applied to test the proposed hypotheses using survey data collected from 200 rice farmers in Mojolaban Sub-district, Sukoharjo District, Central Java, Indonesia. The results show that institutional trust is the strongest direct predictor of farmers’ commitment to agricultural land use (β = 0.555, p < 0.001) and agricultural land ownership (β = 0.217, p < 0.001). Meanwhile, interpersonal trust significantly increases farmers' commitment to agricultural land use through increased self-efficacy. In parallel, interpersonal trust significantly increases farmers' commitment to agricultural land ownership through place attachment. The findings also reveal a strong positive relationship between farmers’ commitment to agricultural land use and their commitment to agricultural land ownership (β = 0.671, p < 0.001). These results highlight that institutional and interpersonal trust play distinct but complementary roles in shaping farmers’ behavioral commitment. This study contributes to the literature on social capital, specifically the trust dimension, by showing that interpersonal and institutional trust are not interchangeable in the context of rural agricultural environments in Indonesia, Southeast Asia. Policy efforts should therefore focus on strengthening institutional credibility, improving extension services, and reinforcing farmer groups to enhance trust, thereby supporting long-term agricultural sustainability.